AUDIT MANAJEMEN FUNGSI PENGADAAN: STUDI BIBLIOMETRIC VOSVIEWER DAN PUBLISH OR PERISH YANG TERINDEX GOOGLE SCHOLLAR - Melki Wijaya; Agum Murtaib; Alfin Nathanael; Sholahuddin Sholahuddin; Siti Rodiah (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research discusses audits of procurement functions indexed in Google Scholar from 2019-2023 using bibliometric methods obtained from the publish or perish and Vosviwer applications. In this research, data was taken from 200 documents related to the audit of the procurement function which were indexed on Google Scholar by looking at what trends or phenomena are being experienced by the research subjects and can see articles related to the audit of the procurement function based on what outcomes, variables and phenomena are being used. happen.